Electronic call capturing system vs. paper-based call capturing system a comparative analysis and technology assessment - Edulan, Geoffrey N. (Technology Management Center, 2009)
Pharmaceutical corporations operating in the Philippines are heavily engaged in the marketing and promotions of their products. These ethical-grade drugs are promoted to clients through actual detailing of products and a face-to-face interaction. The validity of the field-force's (Medical Representatives) actual visit to the doctors/s clients is validated by the pharmaceutical companies via call capture systems : paper based and electronic form. The technology in call capture system currently used by the pharmaceutical corporations in the Philippines is predominantly paper-based and a few are engaged in the use of the electronic form of call capture. Most of the paper-based users are local corporations and a majority of multinational corporations (MNC) already use the electronic form of call capture system. Middle-large MNC's are beginning to adopt the same system as well. Technology enablers are readily available in the country. There a number of third-party software vendors and technology hardware suppliers (smartphones) investing here in the Philippines and are offering their services to pharma companies. Although the initial focus of real-time computing software developers is on supply-chain management, they soon saw the opportunity of its use on corporations engaged in sales and marketing with field-based employees as end-users. This study compares the response of both the electronic and paper-based call capture system end-users and suggests recommendations for possible technology migration and adoption. Although the transition phase from paper-based to electronic form is not the main focus of this study, a pattern seen on the response of the sample population of the study suggests a technology migration of the paper-based users to the electronic form. This finding is based on the answers/responses gathered from the technology end-users-mostly the paper-based users. The satisfaction ratings, perception and readiness of the technology end-users are measured in this study and the results suggested the readiness of the paper-based users to adopt new technologies possible to improve their work activities and align this with their organization's goals and objectives. On the other hand, electronic call capture systems are already enjoying the benefits of using a sophisticated method in capturing calls hence the performance of their companies in the pharmaceutical corporation rankings-volume wise. This study aims to compare the two technologies, assess the viability of each technology through a survey conducted on its end-users, analyse the response given by the respondents, highlight the benefits, use of acquiring new technologies in their organization's value chain and suggest a recommendation on how to explore new technologies as a technology strategy and competitive advantage.